4D.09: DIFFERENT WAVE FORM CALIBRATION OF CENTRAL AORTIC PRESSURE AFFECTS THE ASSOCIATION TO OUTCOME. (June 2015) - Wassertheurer, S.; Baumann, M.
Abstract : Objective: The impact of different calibration methods on the prognostic power of aortic systolic pressure (aSBP) is only poorly reported in literature. The aim of this work was therefore the prospective investigation of the association of brachial (bSBP) and aortic systolic blood pressures to all cause mortality with special emphasis on different calibration methods for central pressure estimates, in particular brachial systolic and diastolic as well as brachial mean and diastolic pressures. Design and method: 135 Patients were enrolled in a longitudinal, prospective study of arterial stiffness and cardiovascular risk in a cohort suffering from chronic kidney disease stages 2 to 4. Office measurements of bSBP and aSBP were assessed by a validated oscillometric device. Prognostic factors of survival were identified by use of Cox proportional hazards regression models. Results: After a mean follow up duration of 42 months (range: 30 to 50 months) 13 patients died. In univariate Cox analysis, bSBP and aSBP (calibrated using brachial systolic and diastolic pressures) did not significantly predict mortality, only aSBP assessed using measured mean and diastolic pressure calibration was significantly associated with mortality (HR = 1.027, p = 0.008). This remained significant in multivariate analysis after adjustment for age, sex and anthropometric measures and brachial pressure. Conclusions: Within our cohort, only aSBP assessed with measured mean and diastolic pressure predicted mortality and provided highly significant prognostic value.